Detailed findings of videofluoroscopic examination among patients with Parkinson's disease on the effect of cervical percutaneous interferential current stimulation - Nakamori, Masahiro; Toko, Megumi; Yamada, Hidetada; Hayashi, Yuki; Haruta, Azusa; Hiraoka, Aya; Yoshikawa, Mineka; Nagasaki, Toshikazu; Ushio, Kai; Yoshikawa, Kohei; Shimizu, Yoshitaka; Mikami, Yukio; et al. (Frontiers in Neurology, 2023)
Introduction: Parkinson's disease (PD) leads to various types of swallowing disorders. We investigated the effect of cervical percutaneous interferential current stimulation on dysphagia. By conducting detailed qualitative and quantitative analysis of videofluoroscopic examination, we aimed to understand dysphagia in patients with PD and investigate its effects on swallowing function. Methods: Patients received cervical percutaneous interferential current stimulation for 20 min twice a week for 8 weeks. In this exploratory study, we evaluated aspiration/laryngeal penetration, oral cavity residue, vallecular residue, and pharyngeal residue. In addition, we performed temporal analysis. Results: Twenty-five patients were completely evaluated. At baseline, the proportions of laryngeal penetration/aspiration, oral cavity residue, epiglottic vallecula residue, and pharyngeal residue were 40.0%, 88.0%, 72.0%, 60.0%, and 16.0%, respectively. Conversely, pharyngeal transit time, laryngeal elevation delay time, pharyngeal delay time, and swallowing reflex delay were nearly within the normal ranges. Cervical percutaneous interferential current sensory stimulation improved only oral cavity residue at the end of the intervention, from 88.0% to 56.0%. Discussion: Patients with PD demonstrated remarkably high frequencies of residues in the oral and pharyngeal regions. The usefulness of cervical interferential current stimulation was partially demonstrated for oral cavity residue. Considering that PD exhibits diverse symptoms, further accumulation of cases and knowledge is warranted. Trial Registration number: jRCTs062220013